Museum bibliography in the system of documentary communication - Čepytė, Julija (Knygotyra, 2003)
The conception of the system of documentary communication made it possible to speak on the theoretical level about the functioning types of bibliography there (library, publishing house, book trading museum etc. bibliography) which are distinguished according to the organizational feature formulated by O. Korshunov. But there are no special museum bibliography investigations so far. The aim of the report: to reveal the main theoretical aspects of museum bibliography, its conceptions and role in the system of documentary communication.In this report museum bibliography is defined as a kind of bibliography that should answer internal needs of bibliographical information in museums. This is the sphere of secondary information activity, connected with the creation, preservation and usage of bibliographical information there. On investigation, there arises a question whether all the secondary information in museum activity is bibliographic and could it be referred to as museum bibliography? An attempt has been made to answer this question on the basis of understanding the notion "document" and "museum object" in museology as well as the understanding of "object of bibliography" and "document" in the science of bibliography.All the museum objects as belonging to the real world, as well as social and natural sciences information carriers are considered as documents in museology, and secondary information is created about all of them. Although in bibliography science one comes across the same wide understanding of a document (G. Shvetsova-Yodka), but in practice a narrower approach both to the document and to the object of bibliographing is applied. For this reason not all the documents in a wider sense (museum objects) are approached as object of bibliographing in view of bibliography science and practically. In museums bibliographical information should only be secondary information, which is connected with social objects for special fixing of written, audio and visual forms of information.An assumption has been made that the term "documentography" best suits to define secondary information in museums, and it could be considered documentography in a wide sense. Documentography in a narrow sense coincides with the bibliographical information functioning in museums. Documentographic and bibliographical levels absolutely coincide in book museums.Museum bibliography "melting" in the sphere of their information and communication is their infrastructure which guarantees the functioning of bibliographical information in museums (preparation, dissemination and usage) so as all the functions of museums be successfully carried out in the system of documentary communication (the following functions are taken into consideration: memory, communicative, informative, managemental, cultural, educational etc.). While compiling bibliographical (and all the documentographic) information, museum objects (documents) are cognized (they are investigated, described, evaluated etc.). In this way factual data are obtained about the documents. All this enables us to specify the concept of museum bibliography. Museum bibliography is the cognitive and informational museum infrastructure that guarantees the preparation, storage, rendering and application of bibliographical information in them; and all the museum documentography could be considered museum informational and cognitive infrastructure.
Keywords: -